VARIABILITAS SPASIAL DAN TEMPORAL SUHU PERMUKAAN LAUT DAN KLOROFIL-A DI PERAIRAN SELAT MALAKA MELALUI CITRA SATELIT AQUA MODIS - Rahmaidi Azani; Ersti Yulika Sari; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was meant to find out variability temperature and klorofil-a the surfaceeither of sea in spatial or temporal in Malacca strait waters in the Eastern (June - August)during the cycle of recording (2009 - 2012). Methods used is desk analysis is analyzed dataobtained without doing validation and verification in the field. The data in described based ontheories. A pattern of distribution spl very closely relation to patterns of wind that blows in anarea. To scatter spl in malacca strait waters also affected by oscillations climatology. Saji, etal ( 2003 ) in Lubis ( 2012 ) presented the sea surface temperatures in the tropics varying inspatial and temporal. The maximum value temperature the average sea level in malacca straitwaters in the eastern 2009-2012 year reaching 35 oc network. Distribution klorofil-a inmalacca strait waters in the eastern 2009-2012 year average value maximum velocity reached55,40 mg / m3.Key Word: Variability Spatial dan Temporal, Sea SurfaceTemperature , Clorofil-a, MallacaStrait, Aqua Modis.